Analisis Viktimologi terhadap Perlindungan Hukum Korban Penyalahgunaan Data Pribadi dalam Pinjaman Online - Jesa Salsa Billa; Lola Yustrisia (El-Faqih : Jurnal Pemikiran dan Hukum Islam, 2025)
This research examines the misuse of personal data in online loan services with a case study in East Jambi. This case shows the huge losses experienced by victims, both material in the form of the obligation to pay debts that do not belong to them, as well as immaterial in the form of psychological pressure and threats from collectors. The main problem lies in the weak identity verification system of pinjol organizers and the low public awareness in maintaining personal data security. Legal protection has actually been regulated in the Personal Data Protection Law, ITE Law, and mechanisms from the Financial Services Authority (OJK) through the iDebKu service. However, obstacles still arise due to social stigma and the fear of victims reporting. This research emphasizes the importance of legal protection that includes preventive, repressive, and alternative approaches. In addition, OJK's role through iDebKu is very significant in preventing data misuse, although strengthening regulations, improving KYC compliance, and public education are still needed. The results of the study emphasize that victims must file a complaint for every criminal offense so that justice, certainty, and security of personal data can be guaranteed.